Controversies and Conversations: Sarra Copia Sulam (1592–1641) and her Jewish-Christian Salon in Venice - Facchini, Cristiana (Annali di storia dell' esegesi, 2023)
This article offers an introduction to the confrontation about the "immortality of the soulˮ that erupted in Venice between the Jewish poetess Sarra Copia Sulam (1592-1641) and a member of her salon, the priest Baldassarre Bonifaccio.